2006
DOI: 10.1111/j.1745-3933.2006.00182.x
|View full text |Cite|
|
Sign up to set email alerts
|

Masses and angular momenta of contact binary stars

Abstract: Results are presented on component masses and system angular momenta for over a hundred low-temperature contact binaries. It is found that the secondary components in close binary systems are very similar in mass. Our observational evidence strongly supports the argument that the evolutionary process goes from near-contact binaries to A-type contact binaries, without any need of mass loss from the system. Furthermore, the evolutionary direction of A-type into W-type systems with a simultaneous mass and angular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 13 publications
5
65
1
Order By: Relevance
“…Numerous predictions suggested that contact binaries should evolve toward diminishing mass ratios until a total merger the components and dissolution of secondaries [6,46]. This would also agree with the surprising similarity of secondary masses in contact binaries seen by Gazeas and Niarchos [47,53]. If the two sequences in Figure 2 correspond to the respective detached (the upper sequence) and contact configurations (the lower sequence), some systems in the upper sequence must be misclassified as EW's and EB's.…”
Section: Spectroscopy: the Ddo Programsupporting
confidence: 54%
“…Numerous predictions suggested that contact binaries should evolve toward diminishing mass ratios until a total merger the components and dissolution of secondaries [6,46]. This would also agree with the surprising similarity of secondary masses in contact binaries seen by Gazeas and Niarchos [47,53]. If the two sequences in Figure 2 correspond to the respective detached (the upper sequence) and contact configurations (the lower sequence), some systems in the upper sequence must be misclassified as EW's and EB's.…”
Section: Spectroscopy: the Ddo Programsupporting
confidence: 54%
“…Observations show that there are several low mass contact binaries (LMCB) with the total mass close to 1-1.4 M (Gazeas & Niarchos 2006, Gazeas & Stȩpień 2008. The LMCB compared with our models include the first 9 stars from Table 1 of Gazeas & Stȩpień (2008).…”
Section: Evolution Of Contact Binaries and The Suggested New Modelmentioning
confidence: 99%
“…In our study we consider component "1" as the presently more massive one. Our assumption is based on the double-lined spectroscopic observations, where the mass ratio is taken as q = M 2 /M 1 ≤ 1.As shown also by Gazeas & Niarchos (2006), the plots of mass and angular momentum versus orbital period gave a direct evidence of evolution into contact, as well as the evolution of A-type W UMa binaries towards the W-type. Figure 1 (upper panel) shows a plot of mass versus orbital period, as well as the equivalent plots of radius and luminosity in logarithmic scale.…”
mentioning
confidence: 90%